Evaluation of a Screening Method for the Detection of Colistin-Resistant Enterobacteriaceae in Stool. (6th May 2019) - Turbett, Sarah E; Desrosiers, Lisa; Andrews-Dunleavey, Catherine; Becker, Margaret; Walker, Allison Taylor; Esposito, Douglas; Woodworth, Kate Russell; Branda, John A; Rosenberg, Eric; Ryan, Edward T; LaRocque, Regina
Abstract: Emergence of mobile colistin resistance ( mcr )–containing Enterobacteriaceae is a public health threat, prompting enhanced surveillance through the Centers for Disease Control and Prevention. We evaluated a selective culture medium for the isolation of Enterobacteriaceae with non-wild-type colistin minimum inhibitory concentrations, including those with mcr-1 genes, in spiked stool samples.